2016
DOI: 10.1109/tits.2015.2462843
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Adaptive Cruise Controller for Plug-In Hybrid Electric Vehicles Using Nonlinear Model Predictive Control

Abstract: Plug-in hybrid electric vehicles (PHEVs) are promising options for future transportation. Having two sources of energy enables them to offer better fuel economy and fewer emissions. Significant research has been done to take advantage of future route information to enhance vehicle performance. In this paper, an ecological adaptive cruise controller (Eco-ACC) is used to improve both fuel economy and safety of the Toyota Prius Plug-in Hybrid. Recently, an emerging trend in the research has been to improve the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
99
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(99 citation statements)
references
References 30 publications
(24 reference statements)
0
99
0
Order By: Relevance
“…Other studies have also reported significant fuel consumption savings in field and simulation tests of their ACC and CACC control algorithms (see e.g. Eben Li, Li, & Wang, 2013;Kamal, Taguchi, & Yoshimura, 2016;Luo, Liu, Li, & Wang, 2010;Rios-torres & Malikopoulos, 2016;Wang, Hoogendoorn, Daamen, & van Arem, 2014) including controllers for hybrid electric vehicles (Luo, Chen, Zhang, & Li, 2015;Vajedi & Azad, 2015) In a context where there are intersections, the controller proposed by Zohdy and Rakha (2016) provides advice about the optimum course of vehicles equipped with CACC. These researchers reported fuel savings of, on average, 33%, 45%, and 11% for their system compared with the conventional intersection control approaches of a traffic signal, all-way-stop, and roundabout, respectively.…”
Section: Literature Resultsmentioning
confidence: 99%
“…Other studies have also reported significant fuel consumption savings in field and simulation tests of their ACC and CACC control algorithms (see e.g. Eben Li, Li, & Wang, 2013;Kamal, Taguchi, & Yoshimura, 2016;Luo, Liu, Li, & Wang, 2010;Rios-torres & Malikopoulos, 2016;Wang, Hoogendoorn, Daamen, & van Arem, 2014) including controllers for hybrid electric vehicles (Luo, Chen, Zhang, & Li, 2015;Vajedi & Azad, 2015) In a context where there are intersections, the controller proposed by Zohdy and Rakha (2016) provides advice about the optimum course of vehicles equipped with CACC. These researchers reported fuel savings of, on average, 33%, 45%, and 11% for their system compared with the conventional intersection control approaches of a traffic signal, all-way-stop, and roundabout, respectively.…”
Section: Literature Resultsmentioning
confidence: 99%
“…MPC relies on a prediction horizon over which an linear/nonlinear optimization is performed [2], [3]. Nonlinear optimization methods outperform linear ones, but they increase computational time [4], [5]. Although fast numerical algorithms based on Pontryagin's minimum principle have been recently proposed, they still limit the prediction horizon that can be used in real-time [6], [7], [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…We ignore τ d in the rest of calculations and model it as part of uncertainty in Proposition 1. By considering this input, (13) can be rewritten as…”
Section: A Disturbance Setmentioning
confidence: 99%